Relationship Between the Virus Lessons Knowledge and Healthy Living Behavior of Student: In Study Case to the First Grade of Senior High School (X-IPA Class) SMA Negeri 1 Simpang Kiri in New Normal Period - Manik, Siska Pragawati; Mayasari, Ulfayani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
In the new normal, teaching and learning activities can doing by offline, but with the condition that health protocols must be implemented. A person's behavior will be based on knowledge, by obtaining knowledge that is used as the formation of behavior, students can apply the habits they have understood. Students of X IPA class of senior high school SMAN 1 Simpang Kiri have studied virus material in Biology subjects related to COVID-19. Therefore, this study aims to determine the level of students' knowledge about virus material and how students' healthy living behavior in the new normal era in preventing transmission of t Covid and knowing the relationship between knowledge of virus and healthy living behavior of students in  new normal. This research doing with a quantitative approach and manifold correlational research. Samples taken using simple random sampling technique untill 75 respondents were obtained. Data collection technique using test instruments and questionnaires and analyzed with the Kendall's Tau correlation test. Based on the results of the study, it shown that the frequency with which students' knowledge levels highest was in very high category, the highest frequency students healthy behavior in new normal in preventing COVID ransmission in good category, from analysis  Kendall's Tau correlation test, it showed knowledge of virus and healthy living  students in new normal has relationship and regression value of 0.245 and the strength relationship  in  low category  and has a positive direction. From the calculation of coefficient determination, the contribution or magnitude of influence knowledge on behavior is 6%.